PENDIDIKAN AGAMA ISLAM BERDASARKAN SURAT AL-BAQARAH AYAT 233 SEBAGAI UPAYA PENCEGAHAN STUNTING - Nur Kholis (Journal Khafi : Journal Of Islamic Studies, 2023)
This research aims to determine the content of Al-Baqarah verse 233 in preventing stunting. This research was carried out using the library research method. The results of this research show that prevention of stunting based on Al-Baqarah verse 233 can be done by parents committing to providing exclusive breast milk for two full years, a family head is required to provide the best food (balanced nutrition) for his family members (wife and children) in a way that is halal both in terms of obtaining it and its essence, both parents must agree to provide good care by giving full love to their child. It is hoped that the results of this research will be able to contribute to providing educational value to the wider community about the importance of the role of the family in preventing stunting